PERWUJUDAN KEADILAN RESTORATIF DALAM SISTEM PERADILAN PIDANA ANAK MELALUI DIVERSI - Kristina Agustiani Sianturi (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
Every year, children in conflict with the law increases so it is needed to handle an alternative in the way to enforce restorative justice. Bill Number 11 0f 2012 concerning Juvinele  Justice System which is accomodated to handle Juvenile Deliquency for diversion. This regulation defines diversion is the transfer of the settlement of the child to the criminal justice process outside the criminal justice process. Diversion obligates to be done by officers started from police investigator, public prosecutor until judge. The important of handling of diversion process for children in conflict with the law needed a commitment for every single officers to apply diversion process. On the other hand, education and training should be given to every officers especially police investigator, public prosecutor even judge relates handling children in conflict with the law.